Reasonable Foreseeability of Harm as an Element of Nuisance - Hook, Maria (Victoria University of Wellington Law Review, 2016)
A landowner's utility pipe bursts and floods the plaintiff's land. It was reasonably foreseeable that the water would cause flood damage to the plaintiff's land in case of an escape. But it was not reasonably foreseeable that the pipe would burst and, hence, that there would be an escape of water. Can the landowner be liable in nuisance? This paper explores the conceptual implications of the proposition that reasonable foreseeability of harm is an element of liability in nuisance. It argues that, if reasonable foreseeability of harm is an element of nuisance, then nuisance can no longer be thought of as a strict liability tort.